Milly, Molly and Mipper - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z., 2003)
Milly and Molly learn about taking care of the air when they go for a ride on Mipper's motorbike. Includes teaching guide. Suggested level: junior